Adsorption Studies of Acetic Acid on the Surface of Plectonema gracillimum (ZOpf) Hansgirg - Hussain, Sayyed; Farooqui, Mahzar; J. Jadhav, Milind (Asian Journal of Chemistry, 2010)
The aim of present investigation is to study adsorption of acetic acid on Plectonema gracillimum (ZOpf) Hansgirg. The effect of certain parameters on adsorption has been studied. Applicability of Fruendlich adsorption isotherm, Langmuir adsorption isotherm has been tested. Various thermodynamic parameters such as DGº, DHº and DSº are reported. The adsorption power of Plectonema gracillimum (ZOpf) Hansgirg is calculated using batch adsorption process.